AN ONTO-EPISTEMIC INQUIRY REGARDING MEMORY AND COUNTER-MEMORY OF MODERNIST ARCHITECTURE: DEFECTS AND FUTILITY AGAINST NORMS AND CAUSALITY - Kaymaz, Senem; Gleiter, Joerg H. (MIDDLE EAST TECHNICAL UNIV, 2025)
This research is a critical inquiry of the ontological and epistemological status of Modernist Architecture, and is based on the argument that such an inquiry can be made by directing attention to Modernist Architecture's memory and counter-memory. The central hypothesis is that, in addition to having a memory, Modernist Architecture also possesses a countermemory; it actualizes itself through norms and causalities accumulated in its memory. However, it also possesses defects and futilities, and even though it cannot actualize itself through them, they continue to accumulate in the counter-memory of Modernist Architecture. Norms and causality constitute a set of epistemes which encompass the agreed upon characteristics capable of validating Modernist Architecture at any given time, whereas defects and futility represent a distinct set of counterepistemes that encapsulate the singular, intuitive, heretical, and anomalous characteristics of Modernist Architecture. The aim of this research is to develop a methodology that allows for the appraisal of Modernist Architecture from both sets and, through this methodology, to present a fallibilistic possibility for modernist architectural theory. To achieve this goal, the research is transformed into a research program framed by Imre Lakatos' methodology of research programmes. Within this program, norms and causality of Modernist Architecture are inquired in Lakatos' negative heuristic, while its defects and futility are questioned in his positive heuristic. The inquiry to the ontological and epistemological status of Modernist Architecture is limited to its formal, functional, and semantic processes. Throughout the inquiry and in the context of the conclusion, the research reveals speculative interpretations of Modernist Architecture and offers the possibility for critique.
Keywords: Modernist architecture; ontology of modernist architecture; epistemology of modernist architecture; memory; counter-memory; Architecture